Student Perception of the Legitimacy of the People's Representative Council (DPR) After the National Demonstration Action - Yunita Rizky; Agus Wiyaka; Bambang Martin Baru (Al-Makki Publisher, 2026)
This research explores student perceptions of the legitimacy of the People’s Representative Council (DPR) in Indonesia following national demonstration actions. It investigates how political demonstrations have influenced public trust and the perceived legitimacy of the DPR, particularly among the younger generation—students—who play an essential role in shaping democratic processes. Using a qualitative research design, the study examines cognitive, affective, and conative aspects of student perceptions through interviews, observations, and documentary analysis. The results indicate that students are generally critical of the DPR, citing concerns over transparency, accountability, and responsiveness. Although students acknowledge the importance of the DPR, they perceive a gap between its ideal role and its actual performance, particularly in legislative processes. Students expressed disappointment and disillusionment with the DPR, although some still hold hope for reform. The findings highlight a growing trend of youth-driven political participation, with students actively engaging in political discourse and demonstrations. The study suggests that improving communication, transparency, and responsiveness to public aspirations can enhance the legitimacy of the DPR.